Use of organic waste biochar as an innovative alternative for increasing agricultural productivity in small rural communities (Research, Society and Development, 2021)
Biochar, pyrolyzed organic waste for agronomic and environmental purposes, is a viable alternative to improve soil quality in small farm areas in the state of Sergipe, where there is a shortage of water and chemical inputs. This study evaluated the effect of single and simultaneous application of doses (t ha-1) of sewage sludge (SS) and dry coconut shell (CS) on some soil properties and sunflower growth and nutrition (Helianthus annuus L.), in São Cristóvão-SE. The experiment was carried out in a completely randomized scheme, with 6 treatments (1. SE60CS0; 2. SE30CS0; 3. SE20CS10; 4. SE10CS20; 5. SE0CS30; 6. Control (without biochar) and 5 repetitions. In the soil, pH, electrical conductivity, organic carbon, and P, K, and Na concentrations were determined. In the plant, biomass, height, chlorophyll content, and N, P, and K were evaluated. Alone, coconut biochar increased the soil pH but reduced plant N. The sludge biochar did not increase soil pH but improved the soil N and P levels, plant growth (25%), and inflorescence (33%), indicating greater benefits of joint application. In addition to improving productivity, biochar, both from sewage sludge and dry coconut shell, can improve the destination and management of these residues and, at the same time, promote the recycling of nutrients in soil.